Efficiency Management of Educational Systems Development: Approaches and Criteria - Levina, Elena Y.; Ishmuradova, Alfiya M.; Kruchinina, Galina A.; Sayfutdinova, Guzel B.; Novikov, Aleksandr A. (International Review of Management and Marketing, 2016)
The relevance of the study is reasoned by the need to assess the ongoing educational reforms’ implementation, to identify effective strategies, models, mechanisms and technologies. The aim of the paper is to determine the expected criteria and obtained results’ efficiency of the systems’ operation in conditions of high variability of external and internal environment. The paper describes the variety of cycles of the educational system on the example of University training that involves the principle of iteration using in educational development’s management. The authors present certain criteria for management of educational development from the standpoint of functional efficiency of the system defining the management contour of development’s efficiency. This paper is intended for researchers and specialists in the field of educational management at all levels. Keywords: Education, Efficiency Management, Management Criteria, Life Cycles. JEL Classifications: I21, I25, I28